Smart Touch Radiofrequency Catheter Ablation versus Cryoballoon Ablation of Pulmonary Veins in Patients with Paroxysmal Atrial Fibrillation - Hassan, Walid Shehata; Zaky, Sherief Hamed; Mohamed, Khaled Hussein; Ibrahim, Moataz Mohammed (Open Access Macedonian Journal of Medical Sciences, 2020)
AIM: Evaluation of the safety and efficacy of pulmonary veins isolation in patients with paroxysmal atrial fibrillation (AF) using two new different technologies, cryoballoon (CB) ablation and radiofrequency ablation with contact force (CF)-sensing catheters. METHODS: Prospective single-center evaluation, carried out from January 2016 to June 2018 in Critical Care Medicine Department – Cairo University, comparing CF radiofrequency (Thermocool® SmartTouch, Biosense Webster, Inc.) (CF group) with CB ablation (Arctic Front Advance 28 mm CB, Medtronic, Inc.) (CB group), in regards to procedural safety and efficacy, as well as recurrence at 12 months. Overall, 50 consecutive patients were enrolled (25 in each group). RESULTS: The characteristics of patients of both the groups were similar (46.9 ± 11.2 years, the proportion of women 36%, mean documented AF duration 3 ± 2.3 years, mean CHA2DS2-VASc score 1.4 ± 1.3, and mean HAS-BLED 1.4 ± 0.6). Duration of the procedure was significantly lower in the CB group (171.7 ± 15.24 vs. 199.3 ± 18.94 min, p = 0.002), with a longer duration of fluoroscopy and X-ray exposure in the CB group than the CF group but statistically non-significant difference (58.60 ± 11.57 vs. 48.7 ± 13.86 min and 6273 ± 4934 cGy cm² vs. 6853 ± 5069 cGy cm², p = 0.1 and p = 0.2, respectively). Overall complication rate was similar in both groups: 2 (8%) in each group. At 12 months, AF recurrence occurred in 7 patients (28%) in the CF group and in 9 patients (36%) in the CB group (log rank p = 0.682). CONCLUSION: Pulmonary vein isolation using CF-guided RF and second-generation CB leads to comparable single-procedure arrhythmia-free survival at up to 12 months with similar overall complication rate.